Addiction recovery management theory, research, and practice - Kelly, John F.; White, William L. 1947- (Current clinical psychiatry., 2011)
Addiction Recovery Management: Theory, Research, and Practice is the first book on the recovery management approach to addiction treatment and post-treatment support services. Distinctive in combining theory, research, and practice within the same text, this ground-breaking title includes authors who are the major theoreticians, researchers, systems administrators, clinicians and recovery advocates who have developed the model. State-of-the art and the definitive text on the topic, Addiction Recovery Management: Theory, Research, and Practice is mandatory reading for clinicians and all professionals who work with patients in recovery or who are interested in the field.